Problematika Penyelesaian Pelepasan Tanah Wakaf, Tanah Desa, dan Tanah Instansi Pemerintah Untuk Bandara Baru di Yogyakarta - Pitasari, Pitasari; Guntur, I Gusti Nyoman; Kistiyah, Sri (Tunas Agraria, 2020)
Abstract: The relinquishment of rights in the acquisition of land for the development of public interests is influenced by the subject of land rights. In the case of the subject of rights in the form of a legal entity, the relinquishment of rights is not only with the deliberation of the parties to reach an agreement, but approval from the government that often creates problems are required. This study aims to determine the problems and strategies to accelerate the completion of the release of rights from waqf land, village land, and government agency land for New Airport in Special Region of Yogyakarta construction. The research method uses qualitative methods with a descriptive approach. The results of the study are: first the problem of the release is the difficulty of finding a replacement land, the length of time the permit, and there are differences in the meaning of the compensation. Second, the strategy to accelerate the settlement is to provide compensation in the form of money, simplification of licensing for the release from the government on it, and the government agency’s land is contributed to the construction of the airport based on the request for guidance. Basically the mechanism for the release of the three types of land status must obtain permission from the government on it. Keywords: waqf land, village land, government agency land, land acquisition. Intisari: Pelepasan hak dalam pengadaan tanah untuk pembangunan kepentingan umum salah satunya dipengaruhi oleh subjek hak atas tanahnya. Dalam hal subjek hak berupa badan hukum, maka pelepasan hak tidak hanya dengan musyawarah para pihak untuk mencapai kesepakatan, namun diperlukan persetujuan dari pemerintah di atasnya. Persetujuan dari pemerintah di atasnya sering menimbulkan permasalahan sebagai persyaratan pelepasannya. Penelitian ini bertujuan untuk mengetahui problematika dan strategi percepatan penyelesaian pelepasan hak yang berasal dari tanah wakaf, tanah desa, dan tanah instansi pemerintah untuk pembangunan Bandara Baru di Daerah Istimewa Yogyakarta. Metode penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Penelitian ini menemukan bahwa problematika pelepasan tanah adalah kesulitan mencari tanah pengganti, lamanya waktu perizinan pelepasan dari pemerintah di atasnya, dan terdapat perbedaan pemaknaan dalam pemberian ganti kerugian. Berikutnya, strategi percepatan penyelesainnya adalah memberikan ganti kerugian berupa uang, penyederhanaan perizinan pelepasan dari pemerintah di atasnya, dan tanah instansi pemerintah dikontribusikan untuk pembangunan bandara tersebut berdasarkan permohonan petunjuk. Pada dasarnya mekanisme pelepasan dari ketiga jenis status tanah tersebut harus memperoleh izin dari pemerintah di atasnya. Kata Kunci: tanah wakaf, tanah desa, tanah instansi pemerintah, pengadaan tanah.